Determinasi Gaya Kepemimpinan Kepala Sekolah, Iklim Kerja Sekolah, Semangat Kerja Guru Terhadap Kinerja Guru Sekolah Dasar - Restu Cahyono, I Made Surya; Sedana, I Made; Suwindia, I Gede (Institut Agama Islam Daruttaqwa Gresik, 2025)
The phenomenon we observe is that some teachers remain reluctant to make teaching preparations, such as creating syllabi and lesson plans, and there is a less harmonious relationship between teachers and their colleagues. Therefore, the principal is rumored to be less capable of having a good leadership style and creating a conducive work climate. The principal is less able to improve the work spirit and performance of teachers. This study aims to determine the influence of the principal’s leadership style, school work climate, and teacher work spirit, both partially and simultaneously, on teacher performance in Cluster IV, Sawan District. This type of research is quantitative descriptive research. This study uses a survey assessment approach. The data collection technique in survey research uses an instrument in the form of a questionnaire. The data analysis technique used was Multiple linear regression. The results of the study showed that 1) There is a determination between the principal’s leadership style and teacher performance in Cluster IV, Sawan District, 2) There is a determinant between the school work climate and teacher performance in Cluster IV, Sawan District, 3) There is a determinant between teacher work enthusiasm and teacher performance in Cluster IV, Sawan District, 4) There is a joint determinant between the principal’s leadership style, school work climate and work enthusiasm with teacher performance in Cluster IV, Sawan District. The coefficient of determination is 0.523 or 52.3%.